The Application of Communicative Games in Enhancing Students’ Vocabulary Mastery: A Qualitative Study at Senior High School - Atiya Noer Khofifah; Fitrah Yuliawati; Dinar Vincy Yunitaka Bahrudin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the implementation of communicative games in vocabulary teaching in class X-B, analyzing student feedback, and identifying obstacles that emerged throughout the process. A qualitative case study design was used, with one English teacher and 18 purposefully selected students participating. Data collection was conducted through classroom observations and intrviews. The results showed that the games had a positive effect on vocabulary mastery, enthusiasm for learning, and student engagement in class. Before implementation, students' basic vocabulary understanding was minimal, accompanied by weak motivation to learn. After implementation, they appeared more energetic, enthusiastic, and confident in using English during activities. Almost all students responded positively, saying that the lessons were more engaging and less monotonous. The teacher also acknowledged improvements in vocabulary understanding for those who previously struggled. However, issues such as reduced concentration in the afternoon and initial lack of confidence persisted. Overall, communicative games proved to be an effective strategy for enhancing vocabulary mastery and creating a more interactive learning environment.